Similar Outcomes in Treating Major Depressive Disorder With 10 Hz Repetitive Transcranial Magnetic Stimulation (rTMS) Versus Intermittent Theta Burst Stimulation (iTBS): A Naturalistic Observational Study. Issue 2 (March 2022) - Spitz, Nathen A.; Ten Eyck, Patrick; Nizar, Krystal; Boes, Aaron D.; Trapp, Nicholas T.
Abstract : Background: Results reported in the existing literature have shown intermittent theta burst stimulation (iTBS) to be noninferior to 10 Hz repetitive transcranial magnetic stimulation (rTMS) in treating major depressive disorder (MDD) when targeted at the left dorsolateral prefrontal cortex. The goal of this naturalistic observational study was to further explore potential differences between these 2 treatment modalities in treating depression in a real-world cohort. Methods: The participants were 105 patients, 18 years of age or older with a diagnosis of MDD who received standard clinical 10 Hz rTMS or iTBS treatment between 2016 and 2020. Clinical outcomes of depression treatment were assessed on the basis of changes in scores on the Patient Health Questionnaire-9 and on the Montgomery-Asberg Depression Rating Scale. Results: Reduction in depression symptoms was measured with the Patient Health Questionnaire-9 and Montgomery-Asberg Depression Rating Scale from baseline to end of treatment, and no discernible differences in percent change, response, remission, or minimum clinically important difference were found between the 10 Hz rTMS and iTBS treatment groups. Conclusions: Findings in an observational, real-world clinical sample showed no significant differences in outcomes between 10 Hz rTMS and iTBS targeted at the left dorsolateral prefrontal cortex in the treatment of MDD. Because of the shorter treatment time involved, the choice of iTBS may reduce hospital exposure and increase savings and the treatment capacity of clinics without sacrificing effectiveness.